Verdade Tropical, de Caetano Veloso: um Palco de Música Popular, Antropofagia Cultural e Brasilidade Revolucionária - Souza, Héber Ferreira de (2021)
The choice to study an element of Tropicalism, an artistic movement expressing the "climate" of the Brazilian counterculture in the late 1960s, based on Caetano Veloso's hybrid and iconoclastic writing in Verdade Tropical, first published in 1997, is justified, according to Raymond Williams (2011), whose concept of the structure of feelings is paramount to this thesis, because it allows the scrutiny of the changes taking place in Brazil in the terrain of sensibilities, materialized in the arts, music, literature, architecture, fashion, media, cultural and social movements. In the midst of the military dictatorship, anti-hegemony was split between armed conflicts and urban guerrillas, on the one hand, and on the other, the structure of feelings related to a revolutionary brazilianness (RIDENTI, 2010). From a very early age and until now, this controversial artist doubted all certainties and wanted to inaugurate a radical turn in Brazilian popular music, attentive to the insertion of the Brazilian culture in the international scene and to the process by which commercial culture establishes itself as a “fine thing”. Caetano draws inspiration from Oswald de Andrade's “anthropophagy” and from 1920's modernism, among other references, and in his own way he invents musical Tropicalism as an allegory - fragments, montage, dispersion, parody, joy, rebellion, irony. His condition of interpreter of the brazilianness is also highlighted and, for this, dialogues (explicit or implicit) are sought with exponents names of the Brazilian social thought. It was also intended to discuss the chances of thinking the book Verdade Tropical, in light of postcolonial criticism, which announces the "between place", the "hybridism" and the "borders" as loci of subversion. The methodology is of bibliographical nature in order to also analyze the “truth” of Caetano from other sources, such as interviews, newspaper articles and the specialized critics. The subjective report, eyewitness testimony of the Brazilian scene, redefines the notion of "truth", which appears in the title of the work, given the absence of the definite article "the", which allows us to think of it as "a" truth, private and intimate, intertwined with others. We conclude with the understanding of the movement as the “tropicalist explosion”, in other words, the emergence of a singular “structure of feelings”, in which the “significant past”, the “alternative” and the “opposition” are negotiated. The critical fortune explored, finally, rekindles the struggle for the hegemony of historical narratives, in which fragments of generation, represented by excellence in the famous critique by the Marxist Roberto Schwarz, collide with the irreverent prose of the “popular songwriter”.